Study of mathematical models for the removal of Ni2+ from aqueous solutions using Citrullus lanatus rind, an agro‐based waste. (9th October 2018) - Mathangi, J.B.; Helen Kalavathy, M.
Abstract: The defilement of water bodies is going on increasing due to the use of noxious chemicals. In the present study, to alleviate the deadly effects of the heavy metal, the agricultural solid waste Citrullus lanatus rind was used as the precursor for the Nickel ion removal. To remove Nickel from synthetic solution, adsorption studies were conducted. Characterization was done using TGA, SEM and FT‐IR analysis. Various parameters on the adsorption capacity of the adsorbent, isotherm and kinetic studies were carried out. The maximum loading capacity of Ni 2+ was found to be 38.98 mg/g from Langmuir model. Error analyses were also studied to validate the best fit of the curve for isotherm models. The kinetic models were studied to understand the adsorption mechanism. The dynamic behaviour of the fixed column and the modelling of the breakthrough curves were carried out. Desorption studies were performed to consider the reusability of the rind.